Laparoscopic vs. Transabdominal Treatment for Overflow Fecal Incontinence Due to Residual Aganglionosis or Transition Zone Pathology in Hirschsprung's Disease Reoperation - Chen, Feng; Wei, Xiaoyu; Chen, Xiaohua; Xiang, Lei; Feng, Jiexiong (Frontiers in Pediatrics, 2021)
Objective The aim of this study was to describe the details of laparoscopic-assisted reoperative surgery for Hirschsprung’s disease (HSCR) with overflow fecal incontinence, and to retrospectively compare laparoscopic-assisted surgery with transabdominal pull-through surgery. Methods We retrospectively analyzed patients with HSCR with overflow fecal incontinence after the initial surgery in our center between January 2002 and December 2018. Preoperative, peri-operative, and postoperative data were recorded for statistical analysis. Results Thirty patients with overflow fecal incontinence after initial megacolon surgery (17 who underwent transanal pull-through [TA-PT] and 13 who underwent laparoscopic-assisted pull-through [LA-PT]) required a secondary surgery (reoperation with LA-PT [LAR-PT] [n=16] or reoperation with transabdominal pull-through [TR-PT] [n=14]). Indications for reoperation were residual aganglionosis (RA) (7/30, 23.3%) or transition zone pathology (TZP) (23/17, 76.7%). Blood loss was significantly decreased in the LAR-PT group (75±29.2 ml) compared to the TR-PT group (190±51.4 ml) (P=0.001). The length of hospital stay was significantly shorter in the LAR-PT group (10±1.5 days) than that in the TR-PT group (13±2.4 days). No significant differences were found between two groups in surgical methods, defecation function score, or postoperative complications except for wound infection (LAR-PT vs. TR-PT 0 vs 28.6%, P<0.05). Conclusions It is necessary to make a comprehensive analysis of the causes of fecal incontinence after HSCR surgery and make an accurate judgment using appropriate methods. If a reoperation was inevitable for patients with overflow fecal incontinence due to RA or TZP, a comprehensive evaluation prior to the operation is required to maximize the benefit from reoperation. Although laparoscopic reoperation with heart-shaped anastomosis was safe and feasible for patients with failed initial Soave technique, unnecessary reoperation should be avoided as much as possible.